Evaluasi Strategis Kinerja SDM Rekam Medis di Rumah Sakit Islam Gorontalo dalam Mendukung Mutu Layanan Rumah Sakit : Pendekatan Human Resource Scorecard - Lilis Handayani; Ayudhita Cahyani Daud; Nita Anggriani; Hartati Umabaihi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The Human Resource Scorecard is a performance measurement method that focuses on human resources, strategy, and performance. In HRSC, human resource performance is measured through four perspectives: competency, deliverables, high-performance work systems, and efficiency. Performance measurement can be applied to determine the extent of labor quality. The evaluation of performance at Gorontalo Islamic Hospital still found that officers are often late when they come to work. This study aims to determine the performance of medical record officers at Gorontalo Islamic Hospital using the Human Resource Scorecard method. This research is a quantitative study using a descriptive research design. The population in this study were all medical record officers at Gorontalo Islamic Hospital, totaling 30 medical record officers. The sample in this study was taken as a whole (total sampling) from the total population of 30 medical record officers. This study used a questionnaire, and the data was processed using SPSS. Based on the results of the research conducted, the average value of the High Performance Work System (HPWS) is good (70%). Human Resource Deliverable is good (83.3%), Human Resource Efficiency is good (73.3%), and Human Resource Competency has a good value (80%). So there needs to be attention to providing different compensation between high-performing employees and low-performing employees. This is to increase overall employee motivation and performance. Hospitals need to use the Human Resource Scorecard method to measure the performance of medical record officers more specifically and in detail.